THE CONNOTATIVE MEANING OF THE SYMBOLS IN "ISLAND" KOREAN DRAMA - Maria Sabriana; Yeni Probowati; Ari Astutik (EL2J (English Language and Literature Journal), 2023)
This research is conducted to analyze symbols in Island Korean drama. This research aims at explaining the connotation meanings in the Island drama. The researcher uses descriptive qualitative method and content analysis as the research method. The sources of data are 7 selected pictures taken from Island Korean drama. The data is taken from Telegram and Web, then screenshotting scene of the symbol represented in Island Korean drama, and understanding the dialogues of Island Korean drama, after that describing symbol and connotative meaning of each scene of Island Korean drama using Roland Barthes’ theory semiotics and the last is drawing the conclusion. In this research, all of scenes in Island Korean drama have symbol and connotative meaning. Most of them are about bad omens, weapons to kill demons of lust, and demons of lust.